Effet du l’huile de laurier sur la conservation de la viande du dinde - Belghit, Malik Sif; Mahi, Mansour (My University, 2020)
The objective of this work is to highlight the strengths and weaknesses by comparative experimental study of the different parts of the carcass of white meat widely consumed in Algeria. The results of our experimentation revealed the importance of the nutrients (macronutrients and micronutrients) present in the two products examined. The protein estimate revealed an average of 19.18% in the escalope and 16.62% in the pestle of chiken. Cooking enhances sensory aspects. Algeria uses less and less red meat in favor of white meat of all kinds (chicken and turkey). This consumption is very low compared to the neighboring country. This meat helps to even reduce the nutritional imbalance. Unfortunately, health crises have affected the relationship of consumers to their diet in a cyclical way.
Keywords: white meat; sensory